Overexpression of periostin is significantly correlated to the tumor angiogenesis and poor prognosis in patients with esophageal squamous cell carcinoma - Wang, Wei (e-Century Publishing Corporation, 2014)
Recent studies have found that periostin (PN), as a kind of secreted glycoprotein, is closely related to the metastatic potential and prognosis of many kinds of tumors. This study aimed to examine the expression of PN in patients with esophageal squamous cell carcinoma (ESCC) and explore the relationship of PN expression with clinicopathologic factors, tumor angiogenesis and prognosis. The results showed that increased PN protein expression was prevalent in ESCC and was significantly associated with lymphatic metastasis (P=0.008), tumor differentiation (P=0.04), venous invasion (P=0.014) and TNM stage (P=0.001). Additionally, expression of PN was found to be an independent prognostic factor in ESCC patients. High expression of PN protein is closely correlated to the tumor progression and angiogenesis and poor survival of ESCC. Taken together, PN is a promising biomarker to identify individuals with poor prognostic potential and concludes the possibility of its use as a prognostic marker in patients with ESCC.